Pengorganisasian dalam Perspektif Al-Qur’an dan Al-Hadits: (Kajian Tafsir Tematik) - Muhammad Fathurrohman (Tarbiyah Departement collaboration with AMCA, 2016)
In Arabic, the organizing concept termed at-tandhim, which also means running everything according to its function, as well as every member is in accordance with its function, and a bonding of the individual against another, to conduct unity appropriate measures, to the success of the function each. There are two auxiliary words contained in the Qur'an to learn about this organization. The word is shaff and ummat.